An Evaluation of River Bank Erosion in Volcanic Rivers Post Eruption 2010 of Mount merapi - Puji Harsanto, Jazaul Ikhsan, Hirosi Takebayashi (Fakultas Teknik UGM, 2013)
Mt. merapi is one of the most active volcanoes in Indonesia. Its eruptions have caused disasters in downstream areas